Water extracts of charred litter cause opposite effects on growth of plants and fungi. (January 2016) - Bonanomi, Giuliano; Ippolito, Francesca; Senatore, Mauro; Cesarano, Gaspare; Incerti, Guido; Saracino, Antonio; Lanzotti, Virginia; Scala, Felice; Mazzoleni, Stefano
Abstract: Fire, besides affecting plant litter fate in natural ecosystems, is a widely used tool to manage crop residues in agro-ecosystems. In both cases, burning of plant residues produces highly heterogeneous materials, ranging from little affected plant tissues, to charred substrates, up to mineral ashes, whose chemical nature and biological effects are not yet fully clarified. The aim of our study was to assess the effects of litter treated at different temperatures (100, 200, 300, 400 and 500 °C) on saprotrophic fungi, plant pathogenic microbes, and higher plants. To this purpose, we combined a characterization of 48 organic materials by 13 C-CPMAS NMR spectroscopy with a multi-species laboratory bioassay on seven target organisms (one plant and six microbes). Consistent with previous observations, we showed that, as charring temperature increased, litter quality significantly changed, with a progressive loss of O-alkyl C, di-O-alkyl C, and methoxyl and N-alkyl C, coupled with an enrichment in aromatic C, irrespective of plant litter types. Noteworthy, the bioassay showed that untreated litter had a major inhibitory effect on the test plant, while it acted as a suitable substrate sustaining microbial growth. On the contrary, as litter was charred its biochemical quality decreased with increasing temperature because of a progressive disappearance of easily degradable C sources and enrichment of recalcitrant aromatic fractions. Therefore, charred litter became an organic material suitable to sustain plant growth, but was largely inhibitory for microbial saprotrophic growth. This work demonstrates that defining litter quality by 13 C-CPMAS NMR improves our understanding of the substrate preferences of both plant and microbes for different litter types as well as for charred organic materials. Graphical abstract: Highlights: Eight plant litter types were heated at 100, 200, 300, 400, and 500 °C. Organic materials were chemically characterized by solid state 13 C-CPMAS NMR. Neo-formation of aliphatic and aromatic C compounds was observed above 300 °C. Unheated litter was inhibitory, while heated materials promoted plant growth. Untreated litter supported microbial growth while heated materials had opposite effects.